Numerical simulations and optimization of foam filled free-curved surface composite part. (1st May 2022) - Chen, Siyu; Jing, Xishuang; Xie, Xin; Zhang, Chengyang; Xie, Fubao
Abstract: The purpose of this study is to predict the curing deformation of a foam-filled free-curved surface composite part and reduce the occurrence of curing deformation through process optimization. This research introduces a finite element simulation method and an optimization method for forming parameters for a foam-filled free-curved surface composite part. Meanwhile, sample manufacturing experiments and a comparative analysis between the simulation and actual objects were conducted. The results showed that finite element simulation analysis could effectively predict the curing deformation of the composite part. After the optimization simulation analysis of the molding process parameters, it was found that the curing deformation of the foam-filled free-curved surface composite part could be as small as 2.30 mm.